Assessing plasma activated water irrigation effects on tomato seedlings - Aceto, Domenico; Rotondo, Palma Rosa; Porfido, Carlo; Bottiglione, Benedetta; Paciolla, Costantino; Terzano, Roberto; Minafra, Angelantonio; Ambrico, Marianna; Dilecce, Giorgio; Leoni, Beniamino; De Miccolis Angelini, Rita Milvia; Ambrico, Paolo Francesco (Frontiers in Physics, 2024)
The study assesses the efficacy of Plasma Activated Water (PAW) as an innovative irrigation medium for enhancing growth and defense responses in tomato seedlings, both healthy and inoculated with Tomato mottle mosaic virus (ToMMV). PAW, generated through plasma-based technologies, offers a chemical-free alternative to traditional fertilizers, harnessing reactive species formed during plasma discharge to foster biochemical transformations and responses. Biometric measurements revealed significant growth enhancement in PAW-irrigated samples compared to conventional fertilization methods. Biochemical analysis indicated increased levels of antioxidant molecules and pigments in PAW-treated seedlings, suggesting improved photosynthetic activity and stress tolerance capability.Gene expression analysis demonstrated up-regulation of defense genes in PAW-treated plants after exposure to viral infection, potentially enhancing resilience against pathogens. Furthermore, PAW treatment mitigated nutrient deficiencies and restored mineral nutrient distribution in virus-infected plants, reducing crop losses. These findings underscore PAW's potential as a sustainable agricultural solution, promoting plant growth, enhancing defense mechanisms, and mitigating biotic stress caused by virus infection.